Meaning construal of selected novel eponymous verbs in the current political discourse in Poland: A Cognitive Linguistics account - Paszenda, Joanna; Góralczyk, Iwona (Papers in Linguistics, 2025)
The aim of the article is to propose a Cognitive Linguistics analysis of the semantic construal of selected Polish name-based verbal neologisms and occasionalisms currently used in Polish mass media, such as kidawić [←Małgorzata Kidawa-Błońska], jandować [←Krystyna Janda], obajtkować [←Daniel Obajtek]. In particular, eponymous verbs are treated as constructions whose meanings are negotiated in the dynamic interaction between language users on the basis of the local co-text and shared background knowledge. Name-based verbs convey a wide range of rich, context-dependent meanings as well as the speaker’s (usually negative) evaluation in a very condensed manner. Their holistic interpretation is arrived at in the process of conceptual integration. It has been shown that a chain of paragon-like metonymies licenses the understanding of the proper name in the verb’s base. What is more, depending on the context of use, metonymies may be coupled with syntaphoric or metaphorical mapping(s).